Biomineralization in Cave Bacteria—Popcorn and Soda Straw Crystal Formations, Morphologies, and Potential Metabolic Pathways - Koning, Keegan; McFarlane, Richenda; Gosse, Jessica T.; Lawrence, Sara; Carr, Lynnea; Horne, Derrick; Van Wagoner, Nancy; Boddy, Christopher N.; Cheeptham, Naowarat (Frontiers in Microbiology, 2022)
Caves are extreme, often oligotrophic, environments that house diverse groups of microorganisms. Many of these microbes can perform microbiologically induced carbonate precipitation (MICP) to form crystalline secondary cave deposits known as speleothems. The urease family is a group of enzymes involved in MICP that catalyze the breakdown of urea, which is a source of energy, into ammonia and carbonate. Carbonate anions are effluxed to the extracellular surface of the bacterium where it then binds to environmental calcium to form calcium carbonate which then continues to grow in crystal form. Here, we studied bacterial communities from speleothems collected from the Iron Curtain Cave (ICC) in Chilliwack, B.C., Canada to characterize these organisms and determine whether urease-positive (U+) bacteria were present in the cave, and their potential impact on speleothem formation. The ICC is a carbonate cave located on the northside of Chipmunk Ridge, presenting a unique environment with high iron content sediment and limestone structures throughout. With six pools of water throughout the cave, the environment is highly humid, with temperatures ranging between 4–12°C depending on the time of year. Ninety-nine bacterial strains were isolated from popcorn (PCS) and soda straw (SSS) speleothems. These isolates were screened for urease enzymatic activity, with eleven candidates found to be urease positive. After incubation, species-specific crystal morphologies were observed. Popcorn speleothem provided more bacterial diversity overall when compared to soda straw speleothem when examined under a culture-based method. Nearly twice as many U+ isolates were isolated from popcorn speleothems compared to soda straw speleothems. The U+ candidates were identified to the genus level by 16S rRNA analysis, and two isolates underwent whole genome sequencing. Two novel species were identified as Sphingobacterium sp. PCS056 and Pseudarthrobacter sp. SSS035. Both isolates demonstrated the most crystal production as well as the most morphologically- dissimilar crystal shapes in broth culture and found to produce crystals as previously observed in both agar and broth media. PLEASE SEE ATTACHED REVISED MANUSCRIPT FOR TEH REMAINING OF THE ABSTRACT.